Photonic integrated circuits for next generation PONs - Franco , Eduardo Vala (2019)
We are living in a time where communications became essential for most of our lives, whether it's in the business world, or in our own homes. The increasing need of higher bandwidth inhibits other networks other than optical ber based ones. Nowadays communications are responsible for a substantial percentage of our energetic footprint, hence Passive Optical Network(PON) are a strong contender for the next step of network implementation. These networks present a low energy consumption because between the transmitter and the receiver the signal stays in the optical domain. Although the increasing needs of bandwidth is almost across the communication world, certain services/identities need more bandwidth whether is download or upload. It's easy to understand that di erent consumers have unique needs. It's necessary to develop an architecture that serves all the costumers, in other words, there is a need for a network that provides high bitrate tra c to the users that needs it but also a network that serves the low end user that is not interested in this increase of bandwidth and therefore price in ation. There is today technologies yet to be widely implemented like NG-PON2 that were not implemented in a large scale because they dont represent a nancial return to the telecom operators simply because there is not enough user that requires the high bandwidth delivered by NG-PON2. It's necessary to nd a solution that includes not only the modern technologies but also the already implemented ones. With the objective of nding a solution for the problems mentioned before, this dissertation has the objective of designing a Photonic Integrated Circuit(PIC) that aims to be a transceiver of a Multitech Network that will be composed by the following technologies: Video-Overlay, XG-PON e NG-PON2. This dissertation presents an approach on Passive Optical Networks( PON) and the standards of the said technologies as well as a study of the components needed to assemble the transceiver using the programs ASPIC and VPI Photonics . In the end, there will be presented an architecture for the transceiver to be used in a Optical Network Unit(ONU), and the respective mask Layout.